The impact of politics and COVID-19 on graduate STEM international students of color - Rodriguez, Miguel; Mohamed, Mirna; Barthelemy, Ramon (Journal of International Students, 2025)
Political factors and the COVID-19 pandemic have had profound impacts on international students in the U.S. These factors include anti-immigration rhetoric, the policies of the executive branch, and the additional COVID-19 restrictions placed on international students in 2020. In this study, we interviewed international students in graduate STEM programs and asked them about their political opinions and experiences during the pandemic. This article also provides a brief historical overview of immigration policy and how these policies relate to and impact international students. Many of our participants expressed negative emotions regarding President Trump for reasons ranging from his racist rhetoric to his administration’s policies before and during the pandemic.